Creative Industries and Regional Development: Evidence from China - Jitka Kloudova; Jianpeng Zhang (European Regional Science Association (ERSA), 2010)
The creative economy is playing a more and more important role in regional development to generate income and jobs opportunity. At the centre of creative economy, many evidences show that the creative industries are the most dynamic emerging sectors. In many countries, especially in developed countries, the growth rate of creative industries is more than that of GDP and other industries. In this paper, we examined how is the relationship between the ratio of creative industries' value added to GDP and GDP per capital and if the growth rate of creative industries is more than that of secondary industry through the empirical analysis of Chinese 23 regions data. The results show that strong and significant correlations can be found between the ratio of creative industries' value added and the GDP per capital. There is no evidence to show that growth rate of creative industries is deferent that of secondary industry for all the regions. But when we divide the samples as two groups, there is weak evidence to infer that the growth rate of creative industries is more than that of secondary industry for higher GDP per capital regions; on the contrary, there is overwhelming evidence to infer that the growth rate of secondary industry is more than that of creative industries for lower GDP per capital regions.
Keywords: 330; creative industries; secondary industry; regional development; China